Students’ perspective in a private institution high school YAE/DL (Research, Society and Development, 2022)
The objective of this work is to analyze the perceptions of students of the Chemistry discipline of a High School course of Youth and Adult Education (YAE) in Distance Learning (DL) modality of a private teaching institution. A case study was carried out that proposed a reflection on the profile, expectations, and interests of the students. A questionnaire was applied to 92 students from four classes. The results reveal a slight predominance of men, workers, who live with the family and are responsible for their livelihood. The main expectation that led them to attend YAE/DL was to complete the course in less time. Most respondents do not like the discipline of Chemistry but consider it important for its applicability. The subjects evaluated the program offered as satisfactory, which meets their educational and professional expectations. The results suggest the importance of student-teacher and student-school interaction, as the management of this relationship is essential for the student to be successful in learning.